Odpowiedź :
Odpowiedź:
[tex]a)\\\\(4-x)(x+5)(2x-3)=0\\\\4-x=0\ \ \ \ \vee\ \ \ \ x+5=0\ \ \ \ \vee\ \ \ \ 2x-3=0\\\\-x=-4\ \ /\cdot(-1)\ \ \ \ \vee\ \ \ \ x=-5\ \ \ \ \vee\ \ \ \ 2x=3\ \ /:2\\\\x=4\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=-5\ \ \ \ \vee\ \ \ \ x=\frac{3}{2}[/tex]
[tex]b)\\\\(2x^2-x-1)(x+3)=0\\\\(2x^2+x-2x-1)(x+3)=0\\\\(x(2x+1)-(2x+1))(x+3)=0\\\\(2x+1)(x-1)(x+3)=0\\\\2x+1=0\ \ \ \ \ \ \ \ \vee\ \ \ \ x-1=0\ \ \ \ \vee\ \ \ \ x+3=0\\\\2x=-1\ \ /:2\ \ \ \ \vee\ \ \ \ x=1\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-3\\\\x=-\frac{1}{2}\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=1\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-3[/tex]
[tex]c)\\\\x^3+4x^2-2x-8=0\\\\x^2(x+4)-2(x+4)=0\\\\(x+4)(x^2-2)=0\\\\(x+4)(x-\sqrt{2})(x+\sqrt{2})=0\\\\x+4=0\ \ \ \ \vee\ \ \ \ x-\sqrt{2}=0\ \ \ \ \vee\ \ \ \ x+\sqrt{2}=0\\\\x=-4\ \ \ \ \ \ \vee\ \ \ \ x=\sqrt{2}\ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=-\sqrt{2}[/tex]